SEKOLAH LUAR BIASA (SLB) KABUPATEN KUBU RAYA - Khairiyah, Alifah Luthfi; Nurhamsyah, Muhammad; Caesariadi, Tri Wibowo (JMARS: Jurnal Mosaik Arsitektur, 2024)
One of the basic needs for all humans without exception is education as stated in the UUD 1945 article 31 paragraph (1) states that every citizen has the right to education. The education obtained is in accordance with UU RI Number 20 of 2003 concerning the National Education System in article 5 which states that citizens who have physical, emotional, mental, intellectual and/or social disabilities have the right to receive special education, namely special education. Students with physical disabilities or disabilities (blind, hearing impaired, quadriplegic), mental deficiencies (mental retardation), as well as physical and mental limitations are included in the group of Children with Special Needs. The educational medium for children with special needs is the Special School. Special school was established to increase the distribution of educational services for special needs so that every citizen does not experience gaps in obtaining education. By applying the design method proposed by J. Zeisel in 2006, design is carried out objectively by utilizing data collection through field observations and data collection through books, journals and data from relevant agencies/institutions regarding the design object. Having a design area of 2.2 hectares. The Kubu Raya Regency Special School consists of two building masses, namely the school building and the dormitory building. The school building consists of one floor and the dormitory building consists of two floors.